Flavonoid glycosides from the leaves of Aphananthe aspera (Thunb.) Planch. (Cannabaceae) and their chemotaxonomic significance. (April 2019) - Devkota, Hari Prasad; Kawamura, Koji; Sasanuma, Masaki; Watanabe, Masato; Watanabe, Takashi
Abstract: From the leaves of Aphananthe aspera (Thunb.) Planch. (Family: Cannabaceae), six flavonol glycosides, such as quercetin 3- O - β -glucopyranoside (1 ), kaempferol 3- O - β -glucopyranoside (2 ), quercetin 3- O -rutinoside (3 ), kaempferol 3- O -rutinoside (4 ), quercetin 3- O -neohesperidoside (5 ) and kaempferol 3- O -neohesperidoside (6 ) were isolated and identified. Structure elucidation of these compounds was performed on the basis of NMR spectral data. All these compounds were isolated for the first time from the genus Aphananthe. Chemotaxonomic significance and distribution of these flavonoid derivatives among the genera of Cannabaceae are explained in detail. Highlights: Chemical analysis of the leaves of Aphananthe aspera was performed. Six flavonol glycosides were isolated. Isolated compounds were 3- O -glycosides of quercetin and kaempferol. All compounds were isolated for the first time from the genus Aphananthe.